An Investigation of Phase Transformation and Crystallinity in Laser Surface Modified H13 Steel - S. N., Aqida; Brabazon, Dermot; S., Naher (Springer, 2013)
This paper presents a laser surface modification process of AISI H13 tool steel using 0.09, 0.2 and 0.4 mm size of laser spot with an aim to increase hardness properties. A Rofin DC-015 diffusion-cooled CO2 slab laser was used to process AISI H13 tool steel samples. Samples of 10 mm diameter were sectioned to 100 mm length in order to process a predefined circumferential area. The parameters selected for examination were laser peak power, overlap percentage and pulse repetition frequency (PRF). X-ray diffraction analysis (XRD) was conducted to measure crystallinity of the laser-modified surface. X-ray diffraction patterns of the samples were recorded using a Bruker D8 XRD system with Cu K α (λ=1.5405 Å) radiation. The diffraction patterns were recorded in the 2θ range of 20 to 80°. The hardness properties were tested at 981 mN force. The laser-modified surface exhibited reduced crystallinity compared to the un-processed samples. The presence of martensitic phase was detected in the samples processed using 0.4 mm spot size. Though there was reduced crystallinity, a high hardness was measured in the laser-modified surface. Hardness was increased more than 2.5 times compared to the as-received samples. These findings reveal the phase source of the hardening mechanism and grain composition in the laser-modified surface.